Problems of Implementation of Principles of Social Justice and Economic Efficiency in the Mechanism of Charging Personal Income Tax (PIT) in the Russian Federation - Musaeva, Khaibat Magomedtagirovna; Aliev, Basir Khabibovich; Alieva, Elmira Bashirovna; Magomedtagirov, Murad Musaevich; Imanshapieva, Mazika Musabekovna (International Journal of Economics and Financial Issues, 2015)
The main objective of the study is to analyze problems of implementation of principles of social justice and economic efficiency in the existing mechanism of charging personal income tax (PIT) in the Russian Federation and to identify ways of the fullest implementation of the potential of PIT as a fiscal and regulatory instrument of state policy. To substantiate the theoretical principles and practical results of the study we've used the methods of abstraction, induction and deduction, the economic-statistical methods (summarizing and grouping, etc.), as well as the principles of comparative and logical analysis, system and complex approach. The scientific novelty of the work consists in development of proposals and recommendations of scientific and applied sphere aimed at adherence to the principles of social justice and economic efficiency in the mechanism of charging personal income tax (PIT) in the Russian Federation. The main conclusions of the study are to identify problems and to assess ways of the fullest implementation of the potential of PIT as a fiscal and regulatory instrument in the Russian Federation. In particular, the study shows non-adherence to the principles of economic expediency and social orientation in the existing mechanism of calculating and charging personal income tax (PIT) in the Russian Federation. The recommendations for improving the administration of personal income tax and increasing its role as a fiscal and regulatory instrument of tax policy in the Russian Federation are proposed. The experience of the mechanism of charging individual income tax both in the industrialized countries and developing ones is studied; the comparative analysis with the practice of taxation of personal incomes in the Russian Federation is conducted. The analysis of factors curbing growth of volume and level of personal income tax revenues to the consolidated budget of the Russian Federation and the Republic of Dagestan is featured. The expediency of introduction of a progressive scale of personal income taxation, which will permit to implement the fiscal and social potential of personal income tax at the present stage of the Russian Federation to the greatest extent, is shown. The necessity of differentiation of social and property personal income tax deductions depending on the personal income and the reasonability of family considerations when charging personal income tax, as a factor determining the ability of a taxpayer to pay, are substantiated. Keywords: economic efficiency, social justice, excess profit, PIT, individual income tax, charging mechanism, deductions, progression, problems. JEL Classifications: H21; H24; H26